Происхождение удмуртского народа: [монография] / М. Г. Атаманов-Эграпи - Атаманов-Эграпи Михаил Гаврилович (Удмуртия, 2010)
Экземпляры: Селтинская районная библиотека (к/х) (20171019) / Инвентарный номер: 204526 / Цена: / Авт.знак: А 92 / ГРНТИ: 03 / ББК: 63.5(2Рос=Удм)